Design and Implementation of Hiding Secure Information Based Transposition Cipher Technique for National Identification Card (Al-Mansour Journal, 2022)
The Security of information on web has turn into a former thing. In spite of the fact that any message is scrambled utilizing a stronger cryptography method, it can't evade the suspicion of interloper. This paper proposes a methodology in such way that, identity information (ID) is encoded utilizing transposition cipher algorithm and afterward this ciphertext is hiding in person image utilizing LSB method. Also in this paper, a ciphertext and biometric key generation algorithm are combined using an effective algorithm to protect the ID information. The purpose of proposed algorithm is to prevent unauthorized persons from viewing or modifying the data and has resistance to Brute-force attack. The obvious attributes of the individual picture prior and then afterward disguise remained just about the same. This algorithm can provide better security to ID card information. The algorithm has been executed utilizing Matlab.
Keywords: ID card; Biometric; Information hiding; Transposition method; Identification Code.